Exploring the potential effect of phospholipase A2 antibody to extend beef shelf-life in a beef liposome model system. (April 2023) - Chun, Colin K.Y.; Roth, Mary; Welti, Ruth; Richards, Mark P.; Hsu, Wei-Wen; O'Quinn, Travis; Chao, Michael D.
Abstract: The objective of this study was to elucidate the effect of phospholipase A2 (PLA2) and a PLA2 antibody (aPLA2) on phospholipid (PL) hydrolysis in beef and to understand how the altered PL composition may affect lipid oxidation and antioxidant capacity of beef in an in vitro system. Various combinations of PLA2 and aPLA2 were introduced to a beef liposome model system and exposed to a retail display. The PL and free fatty acid (FFA) profiles, antioxidant capacity and lipid oxidation were measured for the liposome system. Key PL classes were reduced and the release of polyunsaturated FFAs was increased with the inclusion of PLA2 in the treatments ( P  < 0.05). There was no inhibition of PL hydrolysis with the addition of aPLA2. PLA2 showed strong antioxidant capacity in the liposome system ( P  < 0.01), but lipid oxidation still increased in samples treated with PLA2 throughout the retail display ( P  < 0.01). Finally, aPLA2 treatments demonstrated potential to decrease lipid oxidation ( P  < 0.01).